Evidence for covalence in a N-donor complex of americium(III) - Adam, Christian; Kaden, Peter; Beele, Björn B.; Müllich, Udo; Trumm, Sascha; Geist, Andreas; Panak, Petra; Denecke, Melissa A. (Dalton transactions, 2013)
The molecular origin of the selectivity of N-donor ligands, such as alkylated bis-triazinyl pyridines (BTPs), for actinide complexation in the presence of lanthanides is still largely unclear. NMR investigations of an Am(nPrBTP)33+ complex with a 15N labelled ligand showed that it exhibits large differences in 15N chemical shift for coordinating N-atoms in comparison to both lanthanide(III) complexes and the free ligand. The temperature dependence of NMR chemical shifts observed for this complex indicates a weak paramagnetism. This fact and the observed large chemical shift for bound nitrogen atoms allow us to conclude that metal-ligand bonding in the reported Am(III) N-donor complex has a larger share of covalence than in lanthanide complexes. This may account for the observed selectivity.